SME Management: (What) Can We Learn from Entrepreneurship Theory? - Freiling, Jorg (Senate Hall, 2008)
Small- and medium-sized enterprises (SMEs) are often regarded as entrepreneurshipdriven. There are many reasons for this. For example, the entrepreneur as a person plays a much more vital role than in large firms and entrepreneurial spirit is not weakened by hierarchies and can more easily pervade the firm. Facing the peculiarities of SMEs, entrepreneurship theory seems to offer a lot to understand their very nature and to derive managerial implications. At present, entrepreneurship theory is not sufficiently connected with SME management and needs to be refined to respond to managerial challenges in evolutionary contexts. It is the purpose of this paper to strengthen this link. To this end, the paper scrutinizes entrepreneurship research and identifies the entrepreneurial functions as a promising stream to locate managerial challenges and to integrate them into a cohesive approach. The model rests upon the execution of the following functions which respond to particular managerial challenges: (1) the innovation function contributes to system renewal, (2) the coordination function (internally) and the market-making function (externally) make system exploitation possible, and (3) the risk management function allows for system protection. A causal model proposes that the situation-specific mix of the entrepreneurial functions explains the strategic and financial performance of small firms.
Keywords: entrepreneurship theory|entrepreneurial functions|innovation|coordination|marketmaking|risk management